1992
DOI: 10.1021/ja00046a025
|View full text |Cite
|
Sign up to set email alerts
|

Metal ion binding properties of dihydroxyacetone phosphate and glycerol 1-phosphate

Abstract: The acidity constants of H(R-MP)", where R-MP1 2" = dihydroxyacetone phosphate (DHAP2") and glycerol 1-phosphate (G1P2"), and the stability constants of the binary M(R-MP) complexes (M2+ = Mg2+, Ca2+, Sr2+, Ba2+, Mn2+, Co2+, Ni2+, Cu2+, Zn2+, Cd2+) were determined by potentiometric pH titrations in aqueous solution (/ = 0.1 M, NaN03; 25 °C). The stability of the ternary Cu(Arm)(R-MP) complexes (Arm = 2,2'-bipyridyl or 1,10-phenanthroline) were also measured. On the basis of recent results for simple phosphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 0 publications
4
44
0
Order By: Relevance
“…(vii) The results given in the lower part of Table 2 confirm the earlier conclusions (see the 15 discussed Cu(DHAP) and Cu(G1P) complexes [52,53]) that a reduced solvent polarity favors M 2+ -hydroxyl interactions.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…(vii) The results given in the lower part of Table 2 confirm the earlier conclusions (see the 15 discussed Cu(DHAP) and Cu(G1P) complexes [52,53]) that a reduced solvent polarity favors M 2+ -hydroxyl interactions.…”
supporting
confidence: 84%
“…Indeed, for Cu(DHAP) and Cu(G1P) it has been shown that in water containing 50% 1,4-dioxane (v/v) the chelated species in equilibrium (5) reach a formation degree of about 45% [52,53]. A similar chelate formation must be anticipated for the corresponding Cd 2+ complexes in solutions with a reduced dielectric constant or permittivity (ε).…”
Section: The Metal Ion Affinity Of Ribose-hydroxyl Groups Is Smallmentioning
confidence: 83%
See 1 more Smart Citation
“…a Value for glycerol-1-phosphate, 258C (Liang et al, 1992). The values for which no reference is given are estimated.…”
Section: Computational Softwarementioning
confidence: 99%
“…For instance, the acid and Mg complex dissociation constants of GAP are difficult to obtain because of its instability and conversion to the enolic form (DHAP). Based on the kinetic and structural analysis, Liang et al (1992) postulated that the pK a and pK d for GAP are probably closer to those of glycerol-1-phosphate than to DHAP (Tables III and IV). Therefore, these values were used in the present study.…”
Section: Uncertainty Of the Pk A And Pk D Valuesmentioning
confidence: 99%